Dynamic modelin chemistry: A workbook of computer simulations using electronic spreadsheets - Daniel E Atkinson (N.Simonson, 1990)
The book is organized as a series of exercises to be performed on personal computers running electronic speadsheets software. The models in this book are described using a notation similar to that found in Lotus 1-2-3, Supercalc, Excel, etc. Each exercise begins with a brief introduction to the quantative aspects of the topic to be explored and then provides detailed directions for building the preadsheet model on virtually any personal computer and preadsheets program. Exercises are divided into a Lessons section and Problems section